Clinical outcomes of heart-team-guided treatment decisions in high-risk patients with aortic valve stenosis in a health-economic context with limited resources for transcatheter valve therapies. Issue 6 (2nd November 2019) - Bakelants, Elise; Belmans, Ann; Verbrugghe, Peter; Adriaenssens, Tom; Jacobs, Steven; Bennett, Johan; Meuris, Bart; Desmet, Walter; Rega, Filip; Herijgers, Paul; Herregods, Marie-Christine; Dubois, Christope L.
Abstract: Aims: Transcatheter aortic valve implantation (TAVI) is the preferred treatment modality for patients with severe aortic stenosis at high or prohibitive risk for surgical aortic valve replacement (SAVR). We aimed to evaluate real-world outcomes after treatment according to the decisions of the multidisciplinary heart team in a Belgian health-economic context. Methods and results: Four hundred and five high-risk patients referred to a tertiary centre between 1 March 2008 and 31 December 2015 were screened and planned to undergo SAVR, TAVI or medical treatment (MT). Patients undergoing SAVR had lower Society of Thoracic Surgeons scores and Euroscore-II when compared to TAVI or MT (median [IQR]: 6[4–8]; 7[5–10]; 8[6–13]; p < .001 and 6[4–10]; 8[5–15]; 8[4–16]; p = .006). At 1 year all-cause mortality was 14, 17 and 51% with SAVR, TAVI and MT, respectively ( p < .001). Cardiovascular death and disabling stroke occurred in 9, 7 and 35% ( p < .001) and 2, 2.7 and 1.7% ( p = .91). According to Valve-Academic-Research-Consortium–II criteria, device success was 95 and 92% for TAVI and SAVR. The combined safety endpoint at 30 days favoured TAVI (22% vs. 47%) ( p < .001). The combined efficacy endpoint at 1 year was comparable between groups (38 and 40%; p = .703). Finally, hospital stay was shorter with TAVI vs. SAVR (9[6–14] and 16[12–22] days; p < .001). Conclusions: Limited resources for transcatheter valve therapies in Belgium push a significant number of patients to SAVR, while TAVI in even higher risk patients translates into similar outcomes and shorter hospital stay. These findings underscore the need for broadening indications for TAVI, as well as readjustment of the budgetary allocations for hospitals in Belgium.